Simulation of the quantum-confined stark effect in a single InGaN quantum dot - Lee, K; Robinson, J; Rice, J; Na, J; Taylor, R; Oliver, R; Kappers, M; Humphreys, C (2004)
By means of a 3D self-consistent numerical simulation we have calculated the effect of an externally-applied lateral electric field upon a single InGaN quantum dot. Overall, good agreement between the modeling and experimental results was observed. Modeling results support the observation that the quantum-confined Stark effect has both permanent dipole moment and polarizability components.